Morphology, Morphogenesis, and Molecular Phylogeny of a New Freshwater Ciliate, Quadristicha subtropica n. sp. (Ciliophora, Hypotrichia) - Shao, Chen; Gao, Qi; Warren, Alan; Wang, Jingyi (Frontiers in Microbiology, 2021)
The morphology, morphogenesis and phylogenetic position of a new hypotrichous ciliate, Quadristicha subtropica n. sp. collected from a freshwater pond in southern China, were investigated. Quadristicha subtropica n. sp. is characterized as follows: size in vivo 60–115 μm × 25–45 μm; 19–21 adoral membranelles; buccal cirrus near anterior end of endoral and paroral; cirrus IV/3 at about level of buccal vertex; right marginal row begins ahead of buccal vertex; 11–16 right and 12–19 left marginal cirri; dorsal cilia about 5 μm long. The basic morphogenetic process in Quadristicha subtropica n. sp. is consistent with that of the type species, Q. setigera. Phylogenetic analyses based on small subunit ribosomal DNA sequence data reveal that the systematic position of Quadristicha subtropica n. sp. is rather unstable with low support values across the tree and the genus Quadristicha is not monophyletic.